INOVASI PEMBELAJARAN MATEMATIKA BERBASIS MODEL BERBAKAT DAN MEDIA JELLYFISH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PEMECAHAN MASALAH SISWA - Ferda, Selma; Pratiwi, Diani Ayu (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
The low critical thinking and problem-solving abilities of mathematics students prompted this research. Monotonous learning methods, lecture-based learning methods, and the limited use of interactive media and innovative learning models are the emerging problems. This study uses the Berbakat model and Jellyfish media to implement learning enhancements to address this. Improving students' critical thinking and problem-solving abilities is the main objective of this study. There were 16 students of SDN Karang Buah participating in this study in the even semester of the 2024/2025 academic year. This study used Classroom Action Research (CAR). Student skill observation sheets were used to collect qualitative data, and percentage formulas were used to calculate quantitative data at the level of competency achievement to analyze the observation results. The results showed a significant increase. Students' critical thinking abilities increased from 53% in the "quite skilled" criteria at meeting 1 to 88% in the "very skilled" criteria at meeting 4. Similarly, from meetings 1 to 4, problem-solving skills in the "very skilled" criteria increased from 60% to 88%. These results indicate that the use of the Berbakat model and Jellyfish media is effective in improving students' critical thinking and problem-solving abilities.